Fiber modeling and simulation of effective refractive index for tapered fiber with finite element method - Lee H.J.; Abdullah F.; Emami S.D.; Ismail A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fibers; Magnetism; Optical waveguides; Phase matching; Photonics; Refractive index; Silica; Effective refractive index; Silica fibers; Tapered fiber; Transverse electrics; Transverse magnetic; Finite element method